Fabrication and Characterization of an Efficient Inverted Perovskite Solar Cells with POSS Passivating Hole Transport Layer - Bo-Tau Liu; Hong-Ru Lin; Rong-Ho Lee; Nima E. Gorji; Jung-Chuan Chou (Nanomaterials, 2021)
Polyhedral oligomeric silsesquioxane (POSS), featuring a hollow-cage or semi-cage structure is a new type of organic–inorganic hybrid nanoparticles. POSS combines the advantages of inorganic components and organic components with a great potential for optoelectronic applications such as in emerging perovskite solar cells. When POSS is well dispersed in the polymer matrix, it can effectively improve the thermal, mechanical, magnetic, acoustic, and surface properties of the polymer. In this study, POSS was spin-coated as an ultra-thin passivation layer over the hole transporting layer of nickel-oxide (NOx) in the structure of a perovskite solar cell. The POSS incorporation led to a more hydrophobic and smoother surface for further perovskite deposition, resulting in the increase in the grain size of perovskite. An appropriate POSS passivation layer could effectively reduce the recombination of the electron and hole at grain boundaries and increase the short-circuit current from 18.0 to 20.5 mA·cm−2. Moreover, the open-circuit voltage of the cell could slightly increase over 1 V.